Nexus Between Corporate Social Performance And Corporate Financial Performance: Evidences From An Emerging Market - M C, Minimol; Peter, Praveena (The journal of contemporary issues in business and government, 2021)
This study aims to perform a descriptive research on the effect of Corporate Social Responsibility on Corporate Financial Performance in Indian context using the Index S&P BSE 500. The Corporate Social responsibility has been taken more seriously with the effect of amendment in Companies Act 2013, CSR (Policy) Rules (the Act) from April 1, 2014 and hence the data disclosed in Prowess database by these companies are taken for the study from the time period between FY2014 - FY2018. These values are compared with the financial indicators including the firm size and financial performance and risk measures. Evidences of the relationship is been brought through correlation andregression models. There has been a positive relationship identified with the variables Earnings per Share, Net Profit Margin, Return on Net worth, Return on Capital Employed with the Corporate Social Performance of the firms. Dynamic Panel Regression is used for the panel data with an assumption that the previous year financial performance affect the current year performance. Econometric issues which can arise is also addressed using tests of autocorrelation and endogeneity. The study identifies that the firm size and leverage ratio can affect the CSR expenditure with respect to the profitability variables. The study suggests that keeping a control on interest payments and debt position would be helpful for future performance.